Solution:-
1)Subtract first expression from the second and equate to the third;
"\\frac{dx-dy}{y^2+yz+x^2-y^2+xz-x^2}" ="\\frac{dz}{z(x+y)}"
To obtain;
"\\frac{dx-dy}{z(y+x)}=\\frac{dz}{z(x+y)}"
Simplify to obtain;
"d(x-y)=1dz"
Integrate both sides;
"\\int d(x-y)=\\int 1dz"
"x-y+C=z"
"z=x-y+C_1"
Gives the first integral curve.
2)Add the third expression to the second and equate with the first one;
"\\frac{dx}{y^2+yz+x^2}=\\frac{dy+dz}{y^2-xz+x^2+xz+yz}"
Simplify;
"\\frac{dx}{y^2+yz+x^2}=\\frac{dy+dz}{y^2+yz+x^2}"
Multiple both sides with "y^2+yz+x^2" to obtain;
"dx=dy+dz"
"dx=d(y+z)"
Integrate both sides;
"\\int dx=\\int d(y+z)"
"x+C_2=y+z"
"z=x-y+C_2"
Means the equation has only one integral curve;
"z-x+y=C"
Comments
Leave a comment